Mandibular facial talon cusp: Case report - Oredugba Folakemi A (BMC, 2005)
Abstract Background Talon cusp is a supernumerary structure projecting from the dento-enamel junction to a variable distance towards the incisal edge of an anterior tooth. Studies have shown that it consists of enamel, dentine and a variable amount of pulp tissue. Hyperactivity of the enamel organ during morphodifferentiation has been attributed to its formation. Most previous reports have been made concerning the occurrence of this structure on primary and permanent teeth and mostly on the palatal aspect. Only few have been reported on the facial aspect of the teeth. When it occurs, the effects are mainly aesthetic and functional and so early detection and treatment is essential in its management to avoid complications. Case presentation An unusual case of talon cusp on the facial aspect of a mandibular central incisor is reported. Its presence resulted in attrition of the opposing tooth. Reduction of the cusp and topical application of fluoride gel was initiated. Conclusion The management and treatment outcome of talon cusp depends on the size, presenting complications and patient cooperation.